"Come and talk": The insolvency judge as de‐escalator. Issue 3 (29th July 2020) - Hollemans, Ruben; van Dijck, Gijs
Abstract: How insolvency courts handle conflicts is an important aspect of the Directive on preventive restructuring frameworks and it has become more important in the current COVID‐19 crisis, as a result of which insolvencies are or will be on the rise. Insolvency courts are one of the key actors that can impact the length and costs of conflicts, and, consequently, the effectiveness and efficiency of insolvency proceedings. However, there is a lack of empirical research that examines when, why and how insolvency courts prevent actual or potential conflicts. This article reports the results of an empirical study that explored the strategies used by insolvency judges in the Netherlands to resolve conflicts and to prevent a dispute from becoming one. The results show that insolvency courts deploy "under the radar" mediation‐like strategies to prevent actual and potential conflicts involving insolvency practitioners, enhancing the speed and cost‐effectiveness of the winding‐up of cases in the perceptions of stakeholders. Consequently, insolvency judges do not only act as adjudicators in court proceedings, but also take on mediation‐like roles, at least in some jurisdictions. Limitations and challenges of these roles are discussed. The findings of this study are relevant for determining and regulating the roles and tasks of insolvency judges.